Training on Participatory Integrated Climate Services for Agriculture (PICSA) and Local Technical Agroclimatic Comittes (MTA / LTAC) - Navarro-Racines, Carlos Eduardo (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Training on Participatory Integrated Climate Services for Agriculture (PICSA) and Local Technical Agroclimatic Committees (MTA / LTAC) to the DeRISK project team in Hanoi, Vietnam.